Crop insurance program of the PCIC: Integrative report from the five case regions in the Philippines - Celia M. Reyes; Adrian D. Agbon; Christian D. Mina; Arkin Arboneda (Philippine Institute for Development Studies (PIDS), 2017)
Risk is a daily reality especially among agricultural producers in developing countries, thus agricultural insurance is of interest to farmers, policymakers, insurance companies, and development finance institutions. From a survey data of 2,512 farmers, this paper sheds light on the possible factors affecting insurance availment among the farmers in five selected regions in the Philippines. The farmers' reasons for availing of crop include: encouraged by neighbors, friends, relatives and because of the agricultural technicians in the local government unit. Farmers also shared that insurance is a requirement for getting a loan. Among the possible factors for insurance uptake, level of education, farming experience, and membership in farmer organization are significant factors in the availment of crop insurance from the Philippine Crop Insurance Corporation. Increasing coverage rate of crop insurance among farmers remains to be a challenge in a highly subsidized crop insurance program of the Philippines.
Keywords: 330; crop insurance; poverty; risks and shocks in agriculture; Philippine Crop Insurance Corporation